Analysis of Students’ Perceptions of Ethnic and Racial Diversity in Higher Education Environments - Pratama Setiawan; Intan Cahyani Aprilianti (SOCIA: Jurnal Ilmu-Ilmu Sosial, 2026)
Ethnic and racial diversity refers to the existence of various ethnic and racial groups in society that include differences in geographic origin, culture, language, religion and social practices. Ethnic and racial diversity in higher education refers to a group of students, faculty, and staff who come from different ethnic and racial backgrounds. This is a new challenge and opportunity for universities in managing ethnic and racial diversity. Ethnic and racial diversity is an important aspect in creating a conducive and inclusive higher education environment for all students. This research aims to analyze students' perceptions of ethnic and racial diversity in the Sriwijaya University environment. This research uses a quantitative method with a survey method by distributing questionnaires to students at Sriwijaya University with various faculties and various ethnic and racial backgrounds for each student. The research results obtained show that the majority of students have positive perceptions of ethnic and racial diversity at the universities where they study. Positive perceptions from students who think that diversity in the university environment provides benefits in expanding interviews, increasing tolerance, and enriching learning experiences. However, there are also several challenges faced, such as the existence of negative stereotypes and prejudice among ethnic groups. It is hoped that these findings can become the basis for universities to develop more inclusive policies and create a harmonious and tolerant academic environment.